2016
DOI: 10.1186/s13705-016-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Prosumption and the distribution and supply of electricity

Abstract: Background: Increasing numbers of households install renewable energy production systems like photovoltaic panels thereby contributing to a more sustainable energy system. Other developments, like in-home storage or peer-to-peer exchange within a neighbourhood, also contribute to the transition. This paper explores the emerging rise of these prosumers of electricity and its implications, in particular for grid management and electricity supply in the Netherlands. Methods: With the help of an agent-based model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…These models differ with respect to their prosumer interactions and autonomy, as well as in terms of what incentives should be offered for the prosumer‐generated electricity to be consumed locally or sold to the grid. Similar concepts with regard to prosumer interactions with the electricity system and applying different methods can be found in the literature in papers that use the following terms: peer‐to‐peer electricity supply, prosumer community groups, neighborhood electricity trading, and energy communities . An example of a prosumer electricity trading project that is already implemented is the ‘Brooklyn Microgrid,' as investigated by Mengelkamp et al, who examined the project against a set of components identified as being essential for a microgrid energy market.…”
Section: Introductionmentioning
confidence: 94%
“…These models differ with respect to their prosumer interactions and autonomy, as well as in terms of what incentives should be offered for the prosumer‐generated electricity to be consumed locally or sold to the grid. Similar concepts with regard to prosumer interactions with the electricity system and applying different methods can be found in the literature in papers that use the following terms: peer‐to‐peer electricity supply, prosumer community groups, neighborhood electricity trading, and energy communities . An example of a prosumer electricity trading project that is already implemented is the ‘Brooklyn Microgrid,' as investigated by Mengelkamp et al, who examined the project against a set of components identified as being essential for a microgrid energy market.…”
Section: Introductionmentioning
confidence: 94%
“…"Prosumption" was first coined in the 1980s as an umbrella word to describe the then emerging phenomenon of consumers' "do-it-yourself" activities [19]. The prosumption concept has since been advanced by scholars in consumer studies [20] and socio-economic studies [16,[21][22][23]. Ritzer [16] define prosumption as a continuum of relations involving both producers and consumers in the co-creation of goods and services.…”
Section: Prosumer Value Co-creation and Social Innovation In The Shamentioning
confidence: 99%
“…Energies 2019, 12, x FOR PEER REVIEW 3 of 34 management [18] and grid design strategies [19]. ABMs have also been used to predict price of energy trading in smart grids by the use of incomplete information by different agents to optimize their own utility [20].…”
Section: Electricity Markets and Grid Balancingmentioning
confidence: 99%
“…Previous work on the use of ABMs for electricity grids, markets, and the injection of renewables have focused on the effect of prosumption and peer to peer supply and its effect on the grid management [18] and grid design strategies [19]. ABMs have also been used to predict price of energy trading in smart grids by the use of incomplete information by different agents to optimize their own utility [20].…”
Section: Introductionmentioning
confidence: 99%